Improving Understanding of Fiqh of Worship through Practice at State Junior High School 2 Kotabumi - Dewi Kurniawati; Ridho Hidayah; Anita Anita (JISEI: Journal of Islamic Studies and Educational Innovation, 2025)
This research aims to find out how the application of direct practice in learning Islamic jurisprudence at Madrasah Tsanawiyah Negeri 2 can improve students' understanding of Islamic Islamic jurisprudence material. Learning the jurisprudence of worship, which includes procedures for prayer, zakat, fasting and other acts of worship, is often a challenge for students to understand in depth, because it is generally taught theoretically. Therefore, this research highlights the importance of practice-based learning models in increasing students' understanding of the jurisprudence of worship. The method used in this research is a qualitative method with a case study approach. Data was collected through classroom observations, interviews with fiqh teachers, as well as tests before and after the implementation of religious practices. The results of the research show that learning the jurisprudence of worship which is carried out using a direct practical approach, such as simulating congregational prayers, implementing zakat, and other worship exercises, can increase students' understanding of the correct procedures for worship. In addition, direct practice helps students to better understand the application of fiqh in everyday life. This research contributes to developing a more effective Islamic jurisprudence learning model, by utilizing practical methods to increase students' understanding of religion. It is hoped that the results of this research can become a reference for other Islamic educational institutions in optimizing the learning of Islamic jurisprudence at the madrasah level.